Association between C-reactive protein, pro-oxidant-antioxidant balance and traditional cardiovascular risk factors in an Iranian population. (March 2013) - Razavi, Akramosadat; Baghshani, Mohammad Reza; Rahsepar, Amir Ali; Ardabili, Hossein Mohaddes; Andalibi, Mohammad Sobhan Sheikh; Parizadeh, Seyyed Mohammad Reza; Tavallaie, Shima; Mousavi, Somayeh; Ghayour-Mobarhan, Majid; Ferns, Gordon
Background: Inflammatory states are known to cause an imbalance in the redox status. We aimed to study the possible associations between pro-oxidant-antioxidant balance (PAB) and serum high-sensitive C-reactive protein (hs-CRP) concentrations and traditional cardiovascular disease (CVD) risk factors in an unselected Iranian population and in groups of individuals with specific disease. Methods: The study was conducted among an unselected population of 758 male subjects. Biochemical markers, including hs-CRP and PAB values, were measured. Results: Serum hs-CRP concentrations were positively associated with serum PAB values (r = 0.260, P ≤ 0.001). Univariate analysis showed that PAB values were statistically higher in individuals who were obese or smokers compared with non-obese and non-smokers individuals (P < 0.01). While serum hs-CRP concentrations were significantly higher in older subjects, subjects with obesity, diabetes mellitus, metabolic syndrome, central obesity, hypertriglyceridaemia, higher low-density lipoprotein cholesterol concentrations, positive history of CVD and lower physical activity than subjects without these risk factors (P < 0.05). Comparing hs-CRP and PAB values in different CVD risk score subgroups showed a significant incremental rise in both parameters as CVD risk score increased (P < 0.05). Using multiple linear regression analysis we found a strong association between PAB values and hs-CRP concentrations. Conclusions: This study showed that among Iranian subjects, the inflammatory marker, hs-CRP, was strongly and positively associated with a marker of oxidative stress and also with several traditional risk factors of CVD. Moreover, the impact of traditional cardiovascular risk factors on hs-CRP concentrations and PAB values differed.